The Determinants of BLUD Performance Reporting at Puskesmas Banggae I, Majene: An Analysis of the Role of Information Technology, Human Resource Competence, and Functional Supervision - Hidayat, La Ode; A, Rizky; Puspitasari, Rian; Indar, Sofyan Hamid (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
Performance reporting of Regional Public Service Agencies (BLUD) is a strategic instrument for strengthening accountability, transparency, and performance-based governance in primary healthcare services. This study aims to analyze the effects of information technology utilization, human resource competence, and functional supervision on BLUD performance reporting at Puskesmas Banggae I, Majene Regency. This study employed a quantitative approach with a causal-associative design. A total of 52 respondents participated in the study, and data were collected using a questionnaire and analyzed through chi-square tests and multiple linear regression. The results show that the three variables simultaneously have a significant effect on BLUD performance reporting (F = 17.746; p = 0.000), with an R Square value of 0.526, indicating that the model explains 52.6% of the variation in performance reporting. Partially, information technology utilization had a significant negative effect (B = -1.610; t = -3.515; p = 0.001), human resource competence had a significant negative effect (B = -1.047; t = -2.571; p = 0.013), while functional supervision had a positive and significant effect (B = 0.529; t = 2.557; p = 0.014). These findings indicate that BLUD performance reporting quality is not determined solely by technology availability and employee capacity, but also by system readiness, technical competency alignment, and effective supervision. Therefore, improving BLUD performance reporting requires integrated information systems, technical capacity strengthening, and continuous functional supervision.Keywords: BLUD; performance reporting; information technology; human resources; supervision